Reconciling Color Vision Models With Midget Ganglion Cell Receptive Fields - Patterson, Sara S.; Neitz, Maureen; Neitz, Jay (Frontiers in Neuroscience, 2019)
Midget retinal ganglion cells make up the majority of foveal ganglion cells in the primate retina. The receptive fields of midget ganglion cells exhibit both spectral and spatial opponency and are implicated in both color and achromatic form vision, yet the exact mechanisms linking their responses to visual perception remain unclear. Efforts to develop color vision models that accurately predict all the features of human color and form vision based on midget ganglion cells provide a case study connecting experimental and theoretical neuroscience, drawing on diverse research areas such as anatomy, physiology, psychophysics, and computer vision. Recent technological advances have allowed researchers to test some predictions of color vision models in new and precise ways, producing results that challenge traditional views. Here, we review the progress in developing models of color-coding receptive fields that are consistent with human psychophysics, the biology of the primate visual system and the response properties of midget retinal ganglion cells.